Between mneme and anamnesis: on the memory and forgetting of the Roma Holocaust. Issue 1 (2nd January 2023) - Kapralski, Slawomir
ABSTRACT: The article argues that what is usually called 'Roma memory of the Holocaust' needs to be differentiated into four types, depending on the combination of two modes ( mneme and anamnesis ) and two genealogies of memory (bottom-up and top-down). The first type is memory unconsciously encoded in culture; the second emerges due to the unblocking of memories by external factors; the third refers to the construction of memories by the Roma movement; and the fourth accounts for individual management of memory. These types correspond with four different aspects of Roma identity: cultural (substance), social (relation), historical (process), and individual (choice).